O mecanismo de crédito de transmissão da política monetária para diferentes setores e modalidades de crédito no Brasil : 1990-2006 - Galle, Juliano Morais (2009)
The economic literature on monetary transmission mechanism points to the existence of the credit channel. The purpose of this study is to evaluate the importance of the credit channel for different types of credit such as industrial and rural credit, among others. Aiso, four indicators of product were considered: GDP of agriculture, services, industry, and civil construction industry. Initially we present the existing literature on the credit channel. Then, this work analyzes the recent dynamic of different forms of credit issued by the Central Bank of BraziI to the Brazilian economy. Yet, it sought to point the various oonstraints of the dynamics of crediting in recent Brazilian experiense. From these ditferent forms of credit, establishing wich one delineates the transmission mechanisms of monetary policy using the VAR model. The results showed that some credit forms are more important as the transmission mechanism of monetary policy. Hence, these results suggest that the credit channel exists in particular ways for different types of credit in the economy.